Electronic Permanent Establishment: An Option For International Taxation On Profits Of Cross Border Business Transactions In The Context Of Digital Economy - Hamdan, Mohammad Abdul-Jalil (Advances in Social Sciences Research Journal, 2019)
This paper bases on the fact that the desire to tax businesses by the source countries is diminishing in increasing volumes to the developed nations which require more standard economic ties. The policies that have been proposed in this paper are flexible and can be extended into use in the future. Utilizing the software that are used in these digital business transactions for the purpose of source taxation can only be done temporarily for some given period of time. When the Internet platforms have fully matured, then the developing countries will be capable of benefitting from the new mediums and thus grow economically. The extent to which e-commerce and Internet platforms will continue to grow is not yet determinable but there is some reliable estimation that can help in the formulation of tax policies. The role of e-commerce to the global economy is clear and indispensable; hence all the countries understand the importance of having a reliable and stable consensus that would set forth the tax policies bounding to all international transactions. However, the process would not be as easy as perceived since the technological and economic growth amongst nations is not uniform. Hence the policies as discussed earlier have to harmonize all the challenges that are experienced by different countries.